STATE PROTECTION UPON ADOLESCENT VICTIM OF INCEST RAPE THROUGH GENDER LENS - Elita Rahmi; Elly Sudarti (Fakultas Hukum, Universitas Diponegoro, 2019)
The state obligations to fulfill and protect the rights of adolescent victim of incest rape post-abortion and other rights have not been exercised during the legal process of investigation until court verdict as it is indicated that the adolescent victim is unfairly detained without due process for illegally practicing abortion. This occasion indicates that the law is being unfair towards the adolescent victim without considering the precondition which inevitably forces the abortion. This article scrutinizes such case of Muara Bulian county in which the local court’s verdict No. 5/Pid.Sus.Anak/2018/PN.Mbn did not accommodate the substantive justice which take stand of the rights of adolescent victim of incest rape. The verdict indicates that such court verdict does not express gender sensitivity to the right of adolescent female victim of incest rape to which the state is obliged to fulfil and protect.